SOFTWARE FOR MODELLING OF PROCESSES OF FLIGHT OPERATION IN AREA OF AERODROME - Чинченко, Ю.В.; Поліщук, С.Т. (Proceedings of National Aviation University (archive), 2012)
Information about theoretical aspects of development of interactive system of provision of guaranteed level of safety of air traffic in aerodrome zone is provided. Set of software products for modelling of processes of flight operation in area of aerodrome is considered.